2010
DOI: 10.1002/pen.21692
|View full text |Cite
|
Sign up to set email alerts
|

Process of grafting styrene onto LLDPE by swelling and suspension copolymerization

Abstract: A technology of swelling and suspension copolymerization was conducted to graft styrene onto linear lowdensity polyethylene (LLDPE). The graft mechanism of styrene with LLDPE had been described by 1 H NMR and IR. The mean particle diameter and size distribution of the products with different proportions of LLDPE to styrene monomer were calculated. The morphology and thermal behavior of copolymers were characterized by scanning electron microscopy and differential scanning calorimetry. The glass transition temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(40 reference statements)
0
4
0
1
Order By: Relevance
“…The break elongation increased about 30 times after addition of 8% LLDPE and 10 mL/g of cyclohexane compared with that of PS. However, the breaking power, tensile strength, and breaking strength decreased with increased cyclohexane compatibilizer . Therefore, the right amount of cyclohexane as compatibilizer could increase the grafting efficiency and improve the toughness of PS.…”
Section: Resultsmentioning
confidence: 94%
“…The break elongation increased about 30 times after addition of 8% LLDPE and 10 mL/g of cyclohexane compared with that of PS. However, the breaking power, tensile strength, and breaking strength decreased with increased cyclohexane compatibilizer . Therefore, the right amount of cyclohexane as compatibilizer could increase the grafting efficiency and improve the toughness of PS.…”
Section: Resultsmentioning
confidence: 94%
“…The polymer product was initially dried in an air recirculation oven at 60 °C for 4 h and finally dried in a vacuum oven for 24 h at room temperature. For polymer characterization of PS/PMMA blends, the literature usually recommends the solvent separation of the PS and PMMA phases . Solvent extraction was not performed here because of the low PMMA contents of the resins, which lead to low yields and purity of recovered PMMA fractions.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the viscosity of this system was severely high, leading to instability of the polymerization system (3,15). Previous studies reported that ethylenestyrene interpolymer (ESI) could toughen PS and improve the compatibility of PS and PE or polypropylene (PP) (16)(17)(18). However, the catalyst used for the preparation of ESI was expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of PS and PE via in situ grafting polymerization to improve the properties of PS/PE blends has attracted much attention. However, only a few studies proposed this process for preparing LDPE/PS interpolymer resin particles in suspension polymerization (2,16).…”
Section: Introductionmentioning
confidence: 99%